Howdy or Hello? Technical and Professional Communications - Anders, Kathy; Hagstrom-Schmidt, Nicole (Open textbook library., 2021)
Technical writing courses introduce you to some of the most important aspects of writing in the worlds of science, technology, and business—in other words, the kind of writing that scientists, nurses, doctors, computer specialists, government officials, engineers, and other professionals do as a part of their regular work. The skills learned in technical writing courses can be useful in other fields as well, including education and social sciences.